The Effect of Obedience and Self-Efficacy Pressure on Audit Judgment with Religiosity as a Moderation Variable (Study at BPK Maluku Province) - Alexander Rivan Gaspersz; Dwi Haryanti; Paul Usmany; Christina Sososutiksno; Jefry Gasperz (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of obedience pressure and self-efficacy on audit judgment with religiosity as a moderation variable in auditors at the Maluku Provincial Financial Audit Agency (BPK). The phenomenon of weak audit judgment often arises due to high obedience pressure, low auditor self-efficacy, and lack of religiosity value in the professional decision-making process. This study uses a quantitative approach with a survey method. Data was collected through a questionnaire distributed to BPK auditors in Maluku Province, then analyzed using moderation regression. The results of the study are expected to strengthen the theory of audit judgment by showing that the pressure of obedience decreases the quality of audit judgment, while self-efficacy and religiosity strengthen the ethical decision of auditors. This research has implications for improving the development of ethics, religiosity, and professionalism of auditors within state financial audit institutions.